MODEL KONSELING PRANIKAH BERORIENTASI PENGEMBANGAN KONSEP-DIRI : Studi Kasus Tentang Persiapan Pernikahan Mahasiswa Etnis Minangkabau di IAIN Imam Bonjol Padang - KENEDI, H. Gusril (2005)
Nowadays, the rate of quarrel and divorce in the society increases, and the experts reveal that the devorce is linked to prepararion of marriage done by spouses. In the mean time, Badan Penasihatan Pembinaan dan Pelestarian Perkawinan (BP4), which is expected to handle this situation, does not play optimum role in providing service. Whereas the students face many problems in manage self-concept to have expected marriage and Unit Pelayanan Bimbingan dan Konseling (UPBK) at unversities particularly at IAIN Imam Bonjol Padang is not able to give optimum service to help the students handle the problems. In the mean time, Charles Williams, D. and Peter McDade has developed premarital counseling to reduce disappointment in marriage, but they do not focus on self-concept development. This research is focused to reveal why Minangnese students feel doubtful to face marriage. The purpose of the study is to describe the effort of exploration, knowledge and understanding, emotional condition, establishment of commitment, and the meaning of all toward students' self-concept. Based on the findings, premarital counseling model can be developed as an effort in helping the students manage self-concept to have expected marriage. Through qualitative study it is found that the students are still not able sufficiently to manage self-concept, and it influenced the effort to have expected marriage. This conclusion is supported by the evidance that the students have low exploration effort, limited knowledge and understanding, unhealthy emotional condition, and weak establishment of commitment, and it is also found that the students have potential problem which preven them to achieve successful marriage. Based on the findings, a hypothetic model of premarital counseling can be developed and it was tested and revised in the field. The final model of premarital counseling has these following characteristics: rationale, vision and mission of premarital counseling, the objectives of premarital counseling, materials of premarital counseling, target population, the implementers of premarital counseling, procedures of premarital counseling, and the evaluation of the success. Premarital Counseling Model developed can be useful to help students manage self-concept to have expected marriage. Therefore, the counselor and lecturers are expected to understand the premarital counseling model as a whole by joining the training because unimpaired understanding and training seem to be the foundation for the counselor and lecturers in implementing this model. Future researchers are also recommended to test the effectiveness of this premarital counseling model at different universities, which have different background by doing adjustment and adaptation, and study more some aspects dealing with the marriage of Minangnese students. The officers of BP4 are suggested to make use of the findings and collaborate with researcher in helping the society to have expected marriage. Parents are recommended to give knowledge about marriage and family life to their children.